Liver stiffness measurement reliability and main determinants of point shear‐wave elastography in patients with chronic liver disease. Issue 4 (30th June 2016) - Fraquelli, M.; Baccarin, A.; Casazza, G.; Conti, C. B.; Giunta, M.; Massironi, S.; Invernizzi, F.; Donato, M. F.; Maggioni, M.; Aghemo, A.; Conte, D.; Colombo, M.
Summary: Background: Liver stiffness (LS) measured by transient elastography (TE) accurately predicts the severity of chronic liver diseases (CLD). Point quantification shear‐wave elastography (pSWE) is a new technique incorporated into a conventional ultrasound system for measuring LS. We evaluated pSWE feasibility, reproducibility and diagnostic accuracy in consecutively recruited CLD patients who concomitantly underwent TE and liver biopsy. Aim: To evaluate pSWE feasibility, reproducibility and diagnostic accuracy in consecutively recruited CLD patients who concomitantly underwent TE and liver biopsy. Methods: Over 2 years 186 CLD patients (116 males, 132 viral hepatitis) consecutively underwent pSWE (10 valid measurements by ElastPQ) blindly performed by two raters. A further operator performed TE. Inter‐observer agreement for pSWE was analysed by intraclass correlation coefficient (ICC) and correlated with histological liver fibrosis (METAVIR). Main determinants of pSWE were investigated by linear regression model. Results: Three hundred and seventy‐two (100%) reliable measurements were obtained by pSWE and 184 by TE (99%). LS was 8.1 ± 4.5 kPa for pSWE with the first rater and 8.0 ± 4.2 kPa with the second one vs. 8.8 ± 3.6 kPa for TE. pSWE ICC was 0.89 (95% CI 0.85‒0.91), not influenced by age, sex, BMI, liver enzymes, liver aetiology. ICC increased over time with year 1 at 0.86 and 95% CI 0.81–0.90 vs. year 2 at 0.92 and 95% CI 0.87–0.95. Liver fibrosis was the only independent determinant of LS on pSWE. The AUROCs for diagnosing F ≥ 2, F ≥ 3 and F = 4 were 0.77, 0.85 and 0.88 for pSWE vs. 0.81, 0.88 and 0.94 for TE. After 1‐year training they were 0.86, 0.94 and 0.91. Conclusion: Point quantification shear‐wave elastography reliably and reproducibly evaluates liver stiffness, matching transient elastography for accuracy after a 1‐year learning curve or 130 examinations.